The Influence of Supervisory Roles and Teachers’ Professional Competence on Learning Quality in Elementary Schools in Gubug District - Heru Ekwanto; Widya Kusumaningsih; Joko Sulianto (Journal of Innovation and Research in Primary Education, 2026)
Learning quality in elementary schools is shaped by multiple professional factors, yet the combined influence of supervisory roles and teachers' professional competence remains empirically understudied, particularly in the Indonesian context. This study examines the partial and simultaneous effects of these two variables on learning quality at elementary schools in Gubug District, Grobogan Regency, Central Java, Indonesia. A quantitative correlational survey design was employed, with 92 teachers selected through proportionate stratified random sampling. Data were collected using validated Likert-scale questionnaires measuring supervisory roles, professional competence, and learning quality, and were analyzed using multiple linear regression. The results indicate that supervisory roles significantly and positively influence learning quality (β = 0.472, R² = 0.275, p < 0.001), as does teachers' professional competence (β = 0.418, R² = 0.251, p < 0.001). Simultaneously, both variables account for 47.7% of the variance in learning quality (R² = 0.477, F(2,89) = 42.76, p < 0.001), with supervisory roles emerging as the slightly stronger predictor. These findings advance a dual-determinant framework of instructional quality, underscoring that sustainable improvements in elementary school learning require the synergistic integration of developmental supervision and continuous teacher professional development.